SEJARAH PENGEMBANGAN KURIKULUM DI INDONESIA SERTA KURIKULUM BAHASA INDONESIA - Marine Manik; Yesha Tarigan; Rosmawaty Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to systematically, comprehensively, and coherently describe the evolutionary transformation of the core elements of the 2013 Curriculum (K13) into the operational architecture of the Merdeka Curriculum, with the 2017 Revised Edition of the Indonesian Language Student Book for Grade 10 as the main object of study. Through a descriptive qualitative approach and a literature study method analyzing academic journals and official curriculum documents, this research shows that the Merdeka Curriculum is not a paradigm that severs historical roots, but rather a dialectical process that refines the legacy of K13. K13 has laid a solid philosophical foundation through the integration of three competency domains (attitudes, knowledge, skills), a scientific approach, a thematic-integrative structure, and authentic assessment. The Merdeka Curriculum then liberates this foundation from various implementation constraints such as teachers' administrative burdens and lack of flexibility by introducing structural innovations including Learning Outcomes (Capaian Pembelajaran/CP) as a replacement for Core Competencies/Basic Competencies (KI/KD), Teaching Modules as a replacement for the rigid Lesson Plans (RPP), and a more holistic diagnostic-formative-summative assessment system. An in-depth analysis of the Grade 10 Indonesian Language Student Book shows that each of its text-type-based chapters is a perfect manifestation of K13 principles that can be directly and creatively adapted into Teaching Modules. This study concludes that a deep mastery of the essence of K13, as reflected in the book, is an absolute prerequisite for teachers to design contextual, differentiated learning that can realize the Pancasila Student Profile.